2007
DOI: 10.1017/s1751731107000213
|View full text |Cite
|
Sign up to set email alerts
|

Developing a HACCP-like system for improving animal health and welfare in organic egg production – based on an expert panel analysis

Abstract: In the process of developing a generic Hazard Analysis and Critical Control Point (HACCP)-like system for securing animal health and welfare in organic egg production, an expert panel analysis was used to perform the initial hazard analysis. Eighteen advisers and researchers in organic egg production were included in the expert panel. In a series of four questionnaires, the expert panel first scored 34 health and welfare problems seen in Danish organic egg production. Based on scorings of severity and occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
0
7
0
6
Order By: Relevance
“…However, despite these occasional disagreements, considerable consensus can be achieved on what constitutes good or poor welfare by using formalized methods such as the Delphi technique (e.g., Whay et al, 2003;Hegelund and Sørensen, 2007). The results show that scientists with experience in animal welfare are capable of integrating a variety of information about animal health, housing, and management to achieve a fair consensus on the level of welfare on the farm.…”
Section: Communicating Scientific Uncertaintymentioning
confidence: 96%
“…However, despite these occasional disagreements, considerable consensus can be achieved on what constitutes good or poor welfare by using formalized methods such as the Delphi technique (e.g., Whay et al, 2003;Hegelund and Sørensen, 2007). The results show that scientists with experience in animal welfare are capable of integrating a variety of information about animal health, housing, and management to achieve a fair consensus on the level of welfare on the farm.…”
Section: Communicating Scientific Uncertaintymentioning
confidence: 96%
“…Because poultry red mite is considered a major hazard to the health and welfare of poultry (Hegelund and Sørensen 2007), we elaborated on all possible risk factors for introduction and spread of D. gallinae by conducting an analysis using the HACCP method. In general, this method was evaluated as very helpful.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It is hypothesized that, in a similar way, the HACCP method can be used for risk factor assessment concerning introduction and spread of D. gallinae on poultry farms. Earlier work demonstrated that poultry red mites are considered the most severe and most frequent hazard in relation to 9 other poultry-related hazards such as pasteurellosis and cannibalism (Hegelund and Sørensen 2007). This paper further elaborates on the identification of the risk factors and critical control points, and presents suggestions for corrective actions.…”
Section: Introductionmentioning
confidence: 89%
“…The use of expert knowledge has shown to be successful in other fields of interest in which technical data are scarce or unavailable. ( 21‐24 )…”
Section: Introductionmentioning
confidence: 99%